2015
DOI: 10.1007/s11051-015-3066-6
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the size and morphology of griseofulvin nanoparticles using polymeric stabilizers by evaporation-assisted solvent–antisolvent interaction method

Abstract: Griseofulvin (GF) is a potential drug for cancer therapy. However, its application is limited by its poor water solubility. Ultrafine GF nanoparticles were prepared through evaporation-assisted solventantisolvent interaction method for improving its solubility. Acetone was used as the solvent and water was used as the antisolvent. It was observed that particle size could be controlled by varying the concentration of GF in acetone. Average particle size was very low, 16 ± 4 and 28 ± 8 nm, when the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…The nature of the polymer and its concentration can affect the particle size [54]. The z-average particle sizes that were measured using DLS, when different polymers were used at varying concentrations to stabilize the particle sizes are given in Table 2.…”
Section: The Effect Of Different Stabilizers and Their Concentrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nature of the polymer and its concentration can affect the particle size [54]. The z-average particle sizes that were measured using DLS, when different polymers were used at varying concentrations to stabilize the particle sizes are given in Table 2.…”
Section: The Effect Of Different Stabilizers and Their Concentrationsmentioning
confidence: 99%
“…Stabilizers control the particle size by getting adsorbed on the particle surfaces and by preventing aggregation. There may not be enough polymer molecules available to form at least a monolayer over the particles at lower concentrations [54]. This lack of availability of sufficient amount of stabilizers to control the growth of the particles resulted in larger particles [54].…”
Section: The Effect Of Different Stabilizers and Their Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same method can be used to produce polymer stabilized drug nanoparticles when the polymer is present in the antisolvent. Here, we report the preparation of GF-PVA nanoparticles with particles size below 30 nm and spherical morphology using EASAI method [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[20,22] GF is a highly hydrophobic drug having low solubility and hence, low bioavailability and it exhibits incomplete absorption through the gastrointestinal tract [23]. We have recently shown that solubility of drugs such as CBZ and GF can be enhanced manifold by nanoformulating it with polymeric stabilizers [15,16].…”
Section: Introductionmentioning
confidence: 99%